The influence of the maternal microbiome on offspring neurodevelopment: a critical review of associations, controversies, and challenges - Bai, Hua; Xu, Yan; Qu, Shen; Li, Borui; Wang, Xinna (Frontiers in Neuroscience, 2026)
The role of the maternal microbiome in offspring neurodevelopment has become a prominent topic in neuroscience, yet its true causal status is under intense scrutiny. This critical review moves beyond conventional deconstructions of popular hypotheses in the field (e.g., “prenatal programming” “windows of opportunity”) to challenge a more fundamental premise. We systematically argue that the currently observed associations along the “microbiota-gut-brain axis” may reflect complex confounding, with macroscopic social factors such as socioeconomic status (SES) being the true underlying drivers. The core thesis of this paper is that the maternal microbiome is, to a great extent, a “biological imprint” of the mother’s living environment, diet, and stress levels—a highly sensitive “proxy” indicator acting as a biological mediator heavily shaped by the environment, rather than solely as an independent driver. By integrating evidence from social epidemiology, we contend that positioning the microbiome alongside factors like SES in a “flattened” network model is misleading. Instead, we propose a Hierarchical Causal Model where socioeconomic factors act as top-level “master regulators,” systematically shaping all downstream biological processes, including the microbiome. Through a critical analysis of interventions such as Fecal Microbiota Transplantation (FMT) and vaginal seeding, this review further exposes the translational predicaments that arise from neglecting this hierarchical structure. Ultimately, this review advocates for a paradigm shift: from searching for a single “microbial panacea” to understanding the microbiome’s true position within the socio-biological system, and proposes a conceptual framework for future research that is more aligned with real-world complexity and endowed with greater sociological imagination.